Community Service Outcomes in Justice-Involved Youth: Comparing Restorative Community Service to Standard Community Service - Church, Abere Sawaqdeh (Criminal justice and behavior, 2021)
Traditional mandated community service (CS) typically consists of picking up trash or performing manual labor, distanced from the community. Some juvenile justice programs have begun to implement restorative community service (RCS) programs that enable youth to complete meaningful CS projects in a shame-free manner alongside community members. This study compared RCS with a standard community service (SCS) program in two counties in Washington State on psychosocial outcomes, including attitudes, peer relationships, school conduct, academic performance, and substance use. Recidivism was also examined. RCS was associated with reduced substance use and fewer school conduct difficulties compared with SCS, and also positively influenced peer relationships and attitudes. These findings suggest that adding a restorative component to CS may improve psychosocial outcomes for justice-involved youth, but there was no evidence that adding a restorative component to CS led to reduced recidivism. Additional systematic studies are needed to determine whether these findings replicate.